THE EXPRESSION OF INOS IN MOUSE EXPERIMENTAL MODEL POINTS TO INFLAMMATORY CONDITIONS ASSOCIATED WITH PARKINSON’S DISEASE - Laiche, Fatima; Djebli, Noureddine (European Scientific Journal, ESJ, 2015)
Parkinson’s Disease (PD) is one of the most common neurodegenerative diseases. Several molecular mechanisms are involved. The objective of conducting this study was to evaluate the expression of iNOS in mouse experimental model of PD. PD was induced through injecting mice with 10 doses of MPTP (25 mg/kg) and probenecid (250 mg/kg). Mice in control group were injected by saline (25 mg/kg). Immunohistochemical stains for iNOS in brain sections were carried out using indirect immunoperoxidase techniques. Study findings showed that there was a significant difference in the expression level iNOS in study groups (P<0.001), and experimental PD group had more expressed iNOS levels compared with control group. Taken together, the present study confirmed the impact of induction of iNOS in the etiology of PD.